2007
DOI: 10.1121/1.2434242
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of penalty mode scattering by rigid splices in lined ducts

Abstract: In lined ducts, incident modes are scattered by axially and circumferentially nonuniform impedance. Experiments and numerical calculations have proved that this mode scattering can reduce the liner performance in some cases. This paper is devoted to the characterization of the penalty mode scattering excited by hard-walled splices which often exist in lined ducts. It is shown that, in the range of small splice angles, the transmission loss may decrease sharply with increasing splice angle when one mode, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Numerical investigations are also possible using the method developed by Watson (1981), by expanding the perturbation within the spliced section in terms of the eigenmodes of an unspliced duct, either lined or unlined; however, there is a question over the completeness of the expansion if lined duct modes are used, since the lined duct equation is not self-adjoint. A version of Watson's method, derived by Pagneux, Amir & Kergomard (1996) and termed the multimodal method, was used to investigate liner splices without flow by Bi et al (2006Bi et al ( , 2007. They found liner splices to have a negligible scattering effect for typical aeroacoustic parameters unless the output was dominated by an especially well attenuated mode, in which case they predicted liner splices could give a significant penalty, and they also found that when the phases of incident modes were incoherent the effect of the splices was reduced compared with when the phases of the incident modes were correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations are also possible using the method developed by Watson (1981), by expanding the perturbation within the spliced section in terms of the eigenmodes of an unspliced duct, either lined or unlined; however, there is a question over the completeness of the expansion if lined duct modes are used, since the lined duct equation is not self-adjoint. A version of Watson's method, derived by Pagneux, Amir & Kergomard (1996) and termed the multimodal method, was used to investigate liner splices without flow by Bi et al (2006Bi et al ( , 2007. They found liner splices to have a negligible scattering effect for typical aeroacoustic parameters unless the output was dominated by an especially well attenuated mode, in which case they predicted liner splices could give a significant penalty, and they also found that when the phases of incident modes were incoherent the effect of the splices was reduced compared with when the phases of the incident modes were correlated.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the incident modes are assumed to have random initial phases. In this case, W out is given as follows [21]:…”
Section: Acoustic Power Attenuation and Transmission Lossmentioning
confidence: 99%
“…Many works, based on analytical or numerical approaches, focused on the determination of the scattering matrix. Some works, e.g., [20] and [21], used analytical formulations for the computation of the scattering matrix for acoustic problems. In these works, the liner's impedance was assumed to be constant along the duct, and could arbitrarily vary along the circumference.…”
Section: Introductionmentioning
confidence: 99%
“…It presents an intrinsic characteristic of the duct element. For this, many researchers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have focused their attention on the use of the scattering matrix in their studies. In these studies, this matrix has been obtained from experimental and theoretical methods.…”
Section: Introductionmentioning
confidence: 99%